(untitled) (African Journal of Public Administration & Management, 2026)
The SDGs provide a globally shared blueprint for tackling diverse and interconnected challenges such as reacting to economic crises, mitigating and adapting to climate change, responding to pandemics, managing migration flows, and countering hybrid threats. In this sense, a public service that is capable of achieving the SDGs would also be able to address the root causes of these issues